A New Class of Low‐Temperature Plasma‐Activated, Inorganic Salt‐Based Particle‐Free Inks for Inkjet Printing Metals. Issue 8 (17th May 2019) - Sui, Yongkun; Dai, Yifan; Liu, Chung Chiun; Sankaran, R. Mohan; Zorman, Christian A.
Abstract: Inkjet printing is rapidly emerging as a means to fabricate low‐cost electronic devices; however, its widespread adoption is hindered by the complexity of the inks and the relatively high processing temperatures, limiting it to only a few metals and substrates. A new approach for inkjet printing is described, based on commercially available, particle‐free inks formulated from inorganic metal salts and their subsequent low‐temperature conversion to metallic structures by a non‐equilibrium, inert gas plasma. This single, general method is demonstrated for a library of metals including gold (Au), silver (Ag), copper (Cu), palladium (Pd), platinum (Pt), lead (Pb), bismuth (Bi), and tin (Sn). As one figure of merit, the resistivities of the printed metals are measured to be between 2× and 10× of the respective bulk metals. Uniquely, it is found that the printed metal films exhibit a very large surface area because of the plasma‐initiated nucleation and growth process, making this technique attractive for sensing device applications. A Bi‐based trace Pb sensor, an Au‐based amyloid‐β42 sensor, and an Au‐based strain gauge are fabricated as representative chemical, biological, and mechanical sensors, and are found to exhibit enhanced sensitivity compared to analogues made with conventional methods. Abstract : Inkjet printing of gold, palladium, silver, platinum, copper, bismuth, lead, and tin is realized by using plasma to convert a unique class of particle‐free metal salt‐based inks. This technique can potentially be used to print chemical, biological, and mechanical sensors with enhanced sensitivity on flexible substrates.